Fatty acid membrane assembly on coacervate microdroplets as a step towards a hybrid protocell model - Tang,T-YD; Hak,CRC; Thompson,AJ; Kuimova,MK; Williams,DS; Perriman,AW; Mann,S (Nature Chemistry, 2014)
Mechanisms of prebiotic compartmentalization are central to providing insights into how protocellular systems emerged on the early Earth. Protocell models are based predominantly on the membrane self-assembly of fatty-acid vesicles, although membrane-free scenarios that involve liquid–liquid microphase separation (coacervation) have also been considered. Here we integrate these alternative models of prebiotic compartmentalization and develop a hybrid protocell model based on the spontaneous self-assembly of a continuous fatty-acid membrane at the surface of preformed coacervate microdroplets prepared from cationic peptides/polyelectrolytes and adenosine triphosphate or oligo/polyribonucleotides. We show that the coacervate-supported membrane is multilamellar, and mediates the selective uptake or exclusion of small and large molecules. The coacervate interior can be disassembled without loss of membrane integrity, and fusion and growth of the hybrid protocells can be induced under conditions of high ionic strength. Our results highlight how notions of membrane-mediated compartmentalization, chemical enrichment and internalized structuration can be integrated in protocell models via simple chemical and physical processes.